2021
DOI: 10.3389/fonc.2021.652262
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TMEM16A in Colorectal Cancer and Its Correlation With Clinical and Pathological Parameters

Abstract: TMEM16A is a recently identified calcium-activated chloride channel (CaCC) and its overexpression contributes to tumorigenesis and progression in several human malignancies. However, little is known about expression of TMEM16A and its clinical significance in colorectal cancer (CRC). TMEM16A mRNA expression was determined by quantitative real time-PCR (qRT-PCR) in 67 CRC tissues and 24 para-carcinoma tissues. TMEM16A protein expression was performed by immunohistochemistry in 80 CRC tissues. The correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…DOG-1 is a member of the transmembrane protein 16 family, featured as a calcium-activated chloride channel and expressed in GIST, but the detailed functions are unknown. Recently, the details of DOG-1 have been revealed gradually by reported expression in poorly differentiated tumors [21,22], such as sarcomatous carcinoma of the liver, in lymph node metastasis of colorectal cancer [23], and as a poor prognostic factor in breast cancer [24]. The clinical significance of DOG-1 positivity in UESL is unclear; however, it may become more evident with the accumulation of cases.…”
Section: Discussionmentioning
confidence: 99%
“…DOG-1 is a member of the transmembrane protein 16 family, featured as a calcium-activated chloride channel and expressed in GIST, but the detailed functions are unknown. Recently, the details of DOG-1 have been revealed gradually by reported expression in poorly differentiated tumors [21,22], such as sarcomatous carcinoma of the liver, in lymph node metastasis of colorectal cancer [23], and as a poor prognostic factor in breast cancer [24]. The clinical significance of DOG-1 positivity in UESL is unclear; however, it may become more evident with the accumulation of cases.…”
Section: Discussionmentioning
confidence: 99%
“…KRAS mutation, which is more common in right-sided colon cancer (RCC) than in left-sided colon cancer (LCC), is correlated with a negative prognosis in LCC patients but not in RCC patients 5 . In addition, KRAS mutation is positively correlated with the TMEM16A protein, a calcium-activated chloride channel associated with tumorigenesis and progression in various cancers 6 . However, patients harboring multiple KRAS mutations have better prognoses than those harboring a single mutation 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TMEM16A can serve as a biomarker for clinical outcomes and breast cancer therapeutic responses to tamoxifen [ 5 ]. In colorectal cancer (CRC), Li et al reported that TMEM16A mRNA expression could be a novel predictive marker of LNM, and TMEM16A expression may be an important regulator of tumor proliferation and metastasis [ 34 ]. Moreover, Liu et al (2015) found that high expression levels of TMEM16A were associated with LNM, higher disease grade, and poor prognosis of gastric cancer (GC) [ 35 ], whereas Liu et al (2012) confirmed a positive correlation between TMEM16A expression and tumor grade in prostate cancer [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…TMEM16A overexpression correlates with improved clinical outcomes following chemotherapy [ 34 ]. Vyas et al reported a strong positive correlation between TMEM16A and ATP7B expressions, which balances the copper level in the body by excreting excess copper into bile and plasma in HNSCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation